2022
DOI: 10.1242/dev.200355
|View full text |Cite
|
Sign up to set email alerts
|

Systematic expression profiling of Dpr and DIP genes reveals cell surface codes in Drosophila larval motor and sensory neurons

Abstract: In complex nervous systems, neurons must identify their correct partners to form synaptic connections. The prevailing model to ensure correct recognition posits that cell surface proteins (CSPs) in individual neurons act as identification tags. Thus, knowing what cells express which CSPs would provide insights into neural development, synaptic connectivity, and nervous system evolution. Here, we investigated expression of dprs and DIPs, two CSP subfamilies belonging to the immunoglobulin superfamily, in Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…DIP-α is expressed in a subset of motor neurons called the Is type and localizes to the axon terminals. 23,24,49 Using a Is motor neuron-specific driver, A8-GAL4, 27,52 we confirmed that Myc-DIP-α localizes to puncta in the motor axon terminal (Figure 6A-B'). However, when the GPI anchor was replaced with a TM domain, DIP-α was redistributed and fewer puncta formed, suggesting that clustered presynaptic localization is partially due to the GPI anchor (Figure 6C-D').…”
Section: Gpi Modifications Have Been Shown To Contribute To the Subce...mentioning
confidence: 58%
See 2 more Smart Citations
“…DIP-α is expressed in a subset of motor neurons called the Is type and localizes to the axon terminals. 23,24,49 Using a Is motor neuron-specific driver, A8-GAL4, 27,52 we confirmed that Myc-DIP-α localizes to puncta in the motor axon terminal (Figure 6A-B'). However, when the GPI anchor was replaced with a TM domain, DIP-α was redistributed and fewer puncta formed, suggesting that clustered presynaptic localization is partially due to the GPI anchor (Figure 6C-D').…”
Section: Gpi Modifications Have Been Shown To Contribute To the Subce...mentioning
confidence: 58%
“…The larval Drosophila neuromuscular junction (NMJ) is an excellent system to examine cell surface proteins, as the circuit is well characterized and easily imaged. Moreover, Dprs and DIPs are endogenously expressed at the larval NMJ, 49 and several Dprs and DIPs are implicated in NMJ development. DIP-α and Dpr10 are known to function in motor axon pathfinding and innervation, 23, 31 and DIP-γ and Dpr11 regulate synaptic growth through the BMP pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these experiments, initial attempts to express Dilp2-FAP and a PKA-R2 RNAi with the motor neuron driver OK6-GAL4 did not produce viable progeny. Therefore, PKA-R2 RNAi was expressed only in type Ib boutons with the Dip-β-GAL4 driver (Wang et al , 2022). Strikingly, the forskolin effect on emptying frequency was eliminated, while kiss and run events were unchanged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most Drosophila larval muscles are innervated by two excitatory glutamatergic MNs, known as type-I big MN (Ib MN) and type-I small MN (Is MN) based on their terminal bouton size (Choi et al, 2004;Lnenicka and Keshishian, 2000). In each hemisegment, ~29 Ib MNs innervate thirty muscle fibers mostly in a one-to-one manner (Hoang and Chiba, 2001;Wang et al, 2022), whereas two Is MNs innervate separate groups of muscles and therefore, are known as the common exciters (Takizawa et al, 2007). Genetic ablation of Is MNs led to an expanded NMJ and an elevated excitatory post-synaptic potential (EPSP) amplitude in healthy bystander Ib MNs Han et al, 2022;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%